Qualitative analysis on EU climate change adaptation strategy in health sector - Vera Dimitrievska; Vladimir Kendrovski (University American College Skopje, 2020)
The study assesses the level of integration of public health measures into national climate change adaptation strategies or action plans in the EU 28 countries in 2017-8, as part of the Pagoda WHO project. Areas covered in the analysis are: governance and policies on climate change and health impact, vulnerability assessment of climate change, integrated climate information into infectious disease surveillance, early warning systems for extreme weather, recent projects on climate change and human health, health effects of climate change, best practices, main risks and priorities protecting from climate change. A qualitative approach was applied in this research study based on responses of 20 questionnaires of WHO European Member States. 15 of the responding countries had developed a climate change health adaptation strategy and an associated implementation plan (75%), and these were approved by the government in 13 countries (65%). The results revealed certain specific areas for technical improvement mainly in strengthening of capacities to ascertain the climate- sensitive disease burden in populations.
Keywords: 330; climate change; health; climate change strategy